ANALISIS PERSEPSI MAHASISWA AKUNTANSI UNIKOM TENTANG MUATAN ETIKA DALAM PENGAJARAN AKUNTANSI KEUANGAN - Anggadini, Sri Dewi; Surtikanti, Surtikanti (Jurnal Riset Akuntansi, 2021)
The development of the world of globalization now is this has brought the influence of the great in the Accounting Education System. The many technologies that I have developed today are like Iinternet, Computerized Idan Ise Imangat Ease a student in developing his knowledge. But, the technology that is increasingly growing is called Ibamalah Ibagi Guarantee for the world of education for Iberasil and I Achieve the maximum results. This Is This Is Depends On Idari The consistency of the world of education in Indonesia is Indonesia. In Indonesia, almost all of the lectures in financial accounting have not included explicit issues in the ethical planning of the Semester I Learning Plan (RPS). By Ikarena, I This Research I Conducted Experiments for Imposition obtained evidence that I gave the Ethical Implications that were integrated into the accounting studies of the Financial Space in the Influence of the Perception of Student Ethics. From the results of analyzing the data I have collected through the questionnaire and the results of the I hypothesized test, Imaka can be concluded as the following. There is a Significant Difference between the Students' Perception of Accounting for the ethics of the preparation of financial statements for Indonesian Indonesian Computer University between students of undergraduate and D3 degrees.